Webinar Sosialisasi Vaksinasi Hepatitis B Pada Forum Mahasiswa Kepulauan Seribu, Jakarta Utara, Indonesia - Seulina Panjaitan, Riong; Purwati, Purwati; Sutriningsih, Sutriningsih; Sagala, Zuraida; Lailatusaadah, Nuke; Clara, Clara; Angely Septihany, Elisabeth (Jurnal Adiguna Pengabdian Masyarakat, 2024)
Viral hepatitis is an infectious disease that is a public health problem in developing countries around the world, including Indonesia. Viral hepatitis can affect the morbidity rate. Hepatitis B is caused by the Hepatitis B virus (HBV). Hepatitis B can be prevented with a safe and effective vaccine that is currently available. The purpose of this community service activity is to provide knowledge to the Thousand Islands Student Forum regarding the definition of Hepatitis B disease, the types of Hepatitis B disease and its causes. In addition, we conducted a socialization activity regarding hepatitis vaccination as a form of prevention effort against Hepatitis B disease. The method used by community service members is the presentation method with the help of powerpoint slides through the google meet application. This activity involved the participation of students from the Morning Pharmaceutical Biotechnology class B, Even Academic Year 2020/2021 and the Thousand Islands Student Forum. The results achieved were increasing knowledge to the Thousand Islands Student Forum about Hepatitis B disease and the Hepatitis B vaccine as seen from the results of throwing questions to the committee. The benefits obtained from this activity such as providing more knowledge and educating the Thousand Islands Student Forum about various types of Hepatitis B vaccines for routine immunization programs as a preventive measure against Hepatitis B disease.